Pyroelectric detection in glycolipid thin film - Kwong, W.L.; Gan, W.C.; Majid, W.H.A.; Hashim, R.; Heidelberg, T. (Elsevier, 2010)
The pyroelectric and dielectric properties of glycolipid thin films have been investigated. The glycolipid under studied is (2-n-decyl-n-tetradecyl)-4-O-maltoside. From the thin film observations using polarizing optical microscopy, glycolipid molecules were found to align homeotropically, which results in non-zero temperature-dependent spontaneous polarization. The pyroelectric coefficient, dielectric constant, dielectric loss tangent and figure of merit of the glycolipid thin films are found to be in the range of 70-105 mu C m(-2) K(-1), 5.9-16, 0.242-0.523 and 24-88 mu C m(-2) K(-1) respectively, depending on the glycolipid concentration. Higher concentration of glycolipid renders higher pyroelectric coefficient but lower dielectric constant and dielectric loss tangent, which then results in a higher figure of merit. (C) 2010 Elsevier B.V. All rights reserved.